2014
DOI: 10.1039/c3ra46723f
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective recognition of an inherently chiral calix[4]arene crown-6 carboxylic acid cone conformer towards chiral aminoalcohols

Abstract: A comparative study was conducted to evaluate the chiral recognition ability of several inherently chiral calixcrown carboxylic acids towards chiral aminoalcohols. 1 H NMR titration experiments indicated that inherently chiral calixcrown carboxylic acids each having a phenolic hydroxyl group possess superior chiral recognition ability to the completely alkylated calixarene derivatives. Particularly, inherently chiral calix[4]crown-6 carboxylic acid cone conformer 10 demonstrated significant enantioselectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 56 publications
3
13
0
Order By: Relevance
“…Ar ecent report has lookeda tt he interactions of chiral aminoalcohols with different inherently chiral calix [4]crowns, including ad ensity functional theory (DFT) study,a nd proposed some features that are important for this. [35] Notably the size of the crown ether should ideally include 6o xygen atoms ( Figure 5: n = 3), which supports the earlier observation by Huang. [32] These results are encouraging in that they demonstrate the strong influence of inherentc hirality in chiral recognition of small biologically relevant molecules.…”
Section: Upperand Lower-rim Functionalisationsupporting
confidence: 85%
See 1 more Smart Citation
“…Ar ecent report has lookeda tt he interactions of chiral aminoalcohols with different inherently chiral calix [4]crowns, including ad ensity functional theory (DFT) study,a nd proposed some features that are important for this. [35] Notably the size of the crown ether should ideally include 6o xygen atoms ( Figure 5: n = 3), which supports the earlier observation by Huang. [32] These results are encouraging in that they demonstrate the strong influence of inherentc hirality in chiral recognition of small biologically relevant molecules.…”
Section: Upperand Lower-rim Functionalisationsupporting
confidence: 85%
“…Others have continued this work and made a number of analogues which have been examined for their ability to discriminate chiral amino alcohols. A recent report has looked at the interactions of chiral aminoalcohols with different inherently chiral calix[4]crowns, including a density functional theory (DFT) study, and proposed some features that are important for this . Notably the size of the crown ether should ideally include 6 oxygen atoms (Figure : n= 3), which supports the earlier observation by Huang .…”
Section: Upper‐ and Lower‐rim Functionalisationsupporting
confidence: 62%
“…This is in contrast with the pinched cone conformation adopted by its monoalkylated products 4 a ‐ 7 a / 4 b ‐ 7 b , and 9 a / 9 b . A scrutiny of literature revealed that it is general for a 1,2‐calix[4]crown ether to adopt a regular conformation and their monoalkylated products to adopt a pinched cone conformation, as long as the newly introduced functional group does not participate in intramolecular bonding with the crown ether unit . This conformational change depends on the number of the free phenolic hydroxyls at the lower rim.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these facts, we proposed an interaction mechanism for 8 a and phenylalaninol. In the first place, the relatively regular cone conformation of 8 a is mainly due to the intramolecular hydrogen bonding between the carboxyl group and an oxygen atom of the crown ether unit . Addition of the guest triggers the acid‐base interaction between the host and guest.…”
Section: Resultsmentioning
confidence: 99%
“…In electromagnetic‐wave systems, [ 2–8 ] by introducing desirable polarization, phase, and amplitude profiles of metasurfaces, anomalous refractions or reflections have been achieved, [ 9,10 ] and complex wavefront modulations, including planar lenses, [ 11–13 ] holograms, [ 14,15 ] and ultrathin cloaking, [ 16–18 ] have been realized. In the acoustic systems, the metasurfaces [ 19–26 ] have also captured the fascination of researchers due to their great potential in practical applications, such as acoustic lenses, acoustic holograms, [ 27–31 ] cloaking, [ 32,33 ] vortex, and self‐bending beams. [ 34–37 ] By capturing additional momenta from the metasurfaces, the incident wave can be deflected into the desired direction based on the momentum matching condition.…”
Section: Introductionmentioning
confidence: 99%